Empathy, Confidence, and Collaboration: Exploring STAD’s Impact on Students’ Social-Emotional Development - Rorimpandey, Rinny Suryani; Wongkar, Yapi Henri; Lengkoan, Fergina; Jein, Maniku; Tatipang, Devilito Prasetyo (Elsya : Journal of English Language Studies, 2025)
Fostering social-emotional skills has become an essential dimension of language education, yet English classrooms often prioritize linguistic proficiency while neglecting affective development. This study addresses that gap by investigating how the Student Teams Achievement Divisions (STAD) cooperative learning model can enhance students’ social-emotional growth, particularly in empathy, confidence, and collaboration within English learning contexts. Using a mixed-methods design, data were collected from nine students in the Nursing Department through interviews, focus groups, reflective journals, and classroom observations, complemented by pre- and post-surveys on social-emotional skills and English performance data. Students participated in structured STAD activities designed to promote cooperative interaction and shared accountability. The findings revealed meaningful gains in empathy as students demonstrated stronger mutual respect, actively supported peers, and showed greater sensitivity toward different abilities and perspectives. Their confidence in using English increased significantly, with participants reporting lower anxiety, greater willingness to speak, and stronger self-assurance in sharing ideas during group discussions. Collaboration also improved, as students expressed higher motivation, enjoyment in teamwork, and more active participation in achieving shared goals. Although challenges such as shyness and uneven participation emerged, these were outweighed by the positive interpersonal dynamics created by STAD. This study contributes evidence that incorporating STAD in English classrooms can simultaneously cultivate empathy, build confidence, and strengthen collaboration, creating inclusive learning environments that support both language acquisition and social-emotional development.